TRANSPORT-AS A FACTOR IN ENSURING THE COMPETITIVENESS OF THE TERRITORY (Web of Technology: Multidimensional Research Journal, 2025)
The task of modern transport is not only to meet the demand of consumers on time, but also to provide quality and timely transport service to production. At the same time, we want to note the fact that the phrases “transportation of goods and passengers” and “provision of quality and timely transportation service to consumers” differ significantly in essence. Freight and passenger transport is typical of the first two stages of transport Development, and in the third stage, which implies the unification of production and transport into a single system, the main task of transport is precisely the provision of quality and timely transport service to consumers.